Buckling Analysis of Cracked, Floating Ice Sheets - Adley, M D; Sodhi, D S (1984)
A buckling analysis of cracked, floating ice sheets is presented; both symmetrical and unsymmetrical shapes were investigated. The finite element method was used for the in-plane analysis as well as the out-of-plane analysis. The results of the analyses of symmetrically shaped ice sheets are compared to those of previous analyses where a radial stress field was assumed for the in- plane stresses, and there is good agreement between them. The results of theoretical analyses are compared to experimental data obtained in small-scale laboratory experiments.